Physiological Responses of Sargassum muticum, a Potential Golden Tide Species, to Different Levels of Light and Nitrogen - Yan, Fang; Li, Lingxue; Yu, Daode; Cui, Cuiju; Zang, Shasha; Xu, Zhiguang; Wu, Hongyan (Frontiers in Ecology and Evolution, 2021)
Sargassum golden tides have bloomed frequently in many sea areas throughout the world. As a potential golden tide alga, physiological and ecological studies of this species have not been frequently explored. To investigate the responses of S. muticum to light and nitrogen, two key environmental factors in golden tide formation, we established three light levels (LL, low light, 10 μmol photons m-2 s-1; ML, medium light, 60 μmol photons m-2 s-1 and HL, high light, 300 μmol photons m-2 s-1) and two nitrogen levels (LN, low nitrogen, 25.0 μM of natural seawater; HN, high nitrogen, 125.0 μM), and cultivated the thalli under different conditions for 12 days before measuring the physiological properties of alga. The results showed that higher light and/or nitrogen levels enhanced the relative algal growth rate. The maximum net photosynthesis rate of alga increased with the light, while it remained unaffected by the nitrogen. The HN treatment had no effect on the apparent photosynthetic efficiency of algae in the LL culture, while increased it in the ML and HL cultures. The irradiance saturation point of photosynthesis was approximately 300 μmol photons m-2 s-1 with no significant difference among the six treatments, except for a slight increase under HLHN in contrast to the LLHN and MLLN treatments. HL treatment decreased the maximum quantum yield of photosynthesis (Fv/Fm) in both nitrogen levels. In the HN culture, ML and HL led to lower values of photoinhibition, indicating higher survivability in the alga. The HN culture led to higher nitrogen uptake but had no effects on Fv/Fm and the contents of pigments and soluble protein, regardless of culture light level. Based on these results, we speculate that drifting individuals of S. muticum would be possible to form a golden tide owing to its rapid growth rate at light level of 300 μmol photons m-2 s-1, when they encountered the sustained lower light level on the sea surface (≤300 μmol photons m-2 s-1). A high nitrogen supply caused by eutrophication of seawater might facilitate this process. Our results can provide important reference for the prediction of S. muticum golden tide.